Reflections on some aspects of interfacial transport phenomena, surfactants, and related flows - Zahaf, Hanene; Alla, Hocine; Velarde, Manuel G. (Frontiers in Mechanical Engineering, 2025)
We reflect here on some aspects of interfacial transport phenomena, surfactants, and related flows. First, we recall concepts basic to the rest of the content. Then we highlight the extraordinary success of the concept of active, self-propelling drops thanks to the availability of microelectronic technologies and microelectromechanical systems that were not readily available in 1994 when the pioneering theoretical predictions by Rednikov, Ryazantsev, and Velarde were published. A digression about the ascent of sap in trees is presented, illustrating conflicting views in the botanical community. Surfactant spreading transport is also discussed, illustrating the conflicting views that exist about the superspreading phenomenon in the scientific community. In all cases, we provide suggestions for further research.